Penggunaan Deiksis Persona dalam novel Tuhan, Izinkan Aku Menjadi Pelacur! karya Muhidin M. Dahlan - Putra, Rifaldo Sal; Manaf, Ngusman (Universitas Negeri Padang, 2024)
There are several objectives of this study in order to explain (1) the type of deyxis and (2) the function of persona deyxis as an illocution or speech act in communication with the novel Tuhan, Izinkan Aku Menjadi Pelacur! created by Muhidin M. Dahlan. In its implementation, the study used a novel data source titled Tuhan, Izinkan Aku Menjadi Pelacur! created by Muhidin M. Dahlan with its publisher, Scripta Manent in 2003. This type of research is qualitative through descriptive techniques. This study was used in the form of a persona deyxis in the novel Tuhan, Izinkan Aku Menjadi Pelacur! created by Muhidin M. Dahlan. The results of this study are as follows. First, we and we found the first persona deixis in singular form: me, -ku, and me, then for the first persona deixis in plural: we and we, the second persona deixis in singular form: you, you, you, you and you. And the third persona's description is plural: they. Secondly, the illocutionary function of the persona excises is as follows. The pleasing function is more realized with the pronominal I and –me; more competitive functions are realized with pronominal I, me and -me; the function of cooperating is more realized with the pronominal me and you; And the contradictory function is more realized with the pronominal me, you, and us.